Cortical Microinfarcts Associated With Worse Outcomes in Patients With Acute Ischemic Stroke Receiving Endovascular Treatment. Issue 9 (September 2020) - Wei, Yufei; Pu, Yuehua; Pan, Yuesong; Nie, Ximing; Duan, Wanying; Liu, Dacheng; Yan, Hongyi; Lu, Qixuan; Zhang, Zhe; Yang, Zhonghua; Wen, Miao; Gu, Weibin; et al.
Abstract : Background and Purpose: We aimed to evaluate the impact of cortical microinfarcts (CMIs) on functional outcome after endovascular treatment in patients with acute ischemic stroke. Methods: In a multicenter registration study for RESCUE-RE (a registration study for Critical Care of Acute Ischemic Stroke After Recanalization), eligible patients with large vessel occlusion stroke receiving endovascular treatment, who had undergone 3T magnetic resonance imaging on admission or within 24 hours after endovascular treatment were analyzed. We evaluated the presence and numbers of CMIs with assessment of axial T1, T2-weighted images, and fluid-attenuated inversion recovery images. The primary outcome was functional dependence or death defined as modified Rankin Scale scores of 3 to 6 at 90 days. Secondary outcomes included early neurological improvement, any intracranial hemorrhage, symptomatic intracranial hemorrhage, and mortality. We investigated the independent associations of CMIs with the outcomes using multivariable logistic regression in overall patients and in subgroups. Results: Among 414 patients (enrolled from July 2018 to May 2019) included in the analyses, 96 (23.2%) patients had at least one CMI (maximum 6). Patients with CMI(s) were more likely to be functionally dependent or dead at 90 days, compared with those without (55.2% versus 37.4%; P <0.01). In multivariable logistic regression analyses, presence of CMI(s) (adjusted odds ratio, 1.78 [95% CI, 1.04−3.07]; P =0.04) and multiple CMIs (CMIs ≥2; adjusted odds ratio, 7.41 [95% CI, 2.48−22.17]; P <0.001) were independently, significantly associated with the primary outcome. There was no significant difference between subgroups in the associations between CMI presence and the primary outcome. Conclusions: Acute large vessel occlusion stroke patients receiving endovascular treatment with CMI(s) were more likely to have a poor functional outcome at 90 days, independent of patients' characteristics. Such associations may be dose-dependent. Registration: URL: http://www.chictr.org.cn ; Unique identifier: ChiCTR1900022154. Abstract : Supplemental Digital Content is available in the text.